Lethal provocation : the Constantine murders and the politics of French Algeria - Cole, Joshua, 1961- (Cornell University Press, 2019)
"Explores the most lethal episode of anti-Jewish violence to happen on French territory in peacetime in the twentieth century, a riot in Constantine, Algeria in 1934 in which 28 people died"--